Geriatric neuro-oncology: from mythology to biology - Weller, Michael; Platten, Michael; Roth, Patrick; Wick, Wolfgang (Current opinion in neurology, 2011)
Purpose of review - Age has remained one of the most important determinants of risk for the development of certain brain tumors, of benefit from and tolerance of brain tumor treatment, and overall outcome. Regarding these three aspects, there are major differences across the spectrum of primary brain tumors depending on specific histology. Here, we review recent advances in understanding the biological basis of the prognostic marker ‘age’ in neuro-oncology. - Recent findings - Contemporary population-based studies confirm the strong prognostic impact of age in many brain tumors. Elderly patients continue to be treated less aggressively than younger patients with the same tumors. However, biological factors may contribute to the negative prognostic impact of age. For instance, among gliomas, mutations of the isocitrate dehydrogenase genes, which are prognostically favorable, are much more common in younger patients. Moreover, complete responses defined by neuroimaging were much less durable in elderly as opposed to younger patients with primary central nervous system lymphoma in the German Primary Central Nervous System Lymphoma Study Group trial. - Summary - A combination of age-adapted patterns of care and treatment-independent, tumor-intrinsic factors contributes to the poorer outcome of elderly patients with brain tumors. These factors need to be better distinguished and understood in order to improve outcome in elderly brain tumor patients.
Gesehen am 21.11.2022